Validação de teste para detectar resistência ao herbicida haloxifop em capim-amargoso - Melo, Ana Vitória Sanches da Silva (Universidade Federal de São Carlos, 2025)
Digitaria insularis is an invasive species that reduces crop yields due to its high competitive capacity for natural resources, and can reduce productivity by up to 80% in annual and perennial crops. Control of this invasive plant is often carried out with ACCase-inhibiting herbicides, which interfere with the synthesis of fatty acids and lead to cell death in susceptible plants, without affecting cultivated crops. However, the continuous and repetitive use of these herbicides has selected resistant genotypes, reducing the effectiveness of chemical control. Resistance is associated with mutations in the gene that encodes the ACCase enzyme, compromising its binding to the inhibitor and reducing the efficiency of herbicides. Given this scenario, monitoring resistance in D. insularis is essential for implementing more efficient management strategies and for understanding the genetic mechanisms involved. The present study aimed to validate, through PCR testing and sequencing, genes for resistance to ACCase-inhibiting herbicides in D. insularis. Eighteen samples of possible resistant genotypes were analyzed, compared with six samples of control plants, known to be susceptible. DNA was extracted using the QIAcube using the DNeasy Plant Kit. The analysis was performed through sequence alignment and comparison, revealing that eight samples presented at least one resistant allele associated with the Trp2027Cys mutation, while one sample demonstrated complete resistance. In conclusion, the resistance of invasive plants to herbicides is a growing concern in the field. Therefore, it is necessary to develop rapid and effective tests to monitor the emergence of resistant genotypes among invasive plants. The test used in this project proved to be efficient in detecting polymorphisms of the ACCAse gene in D. insularis genotypes, indicating that it can be used as an ally in monitoring strategies for resistant genotypes.
Validation of a test to detect resistance to the herbicide haloxifop in sourgrass
Keywords: Resistência à herbicidas; Monitoramento; Capim-amargoso; Inibidores de ACCase; Plant protection; Herbicide resistance; Plant resistance; ACCase inhibitor herbicides resistance; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA